Universal Roulette Wheel (London Journal of Research In Science: Natural and Formal, 2023)
In this brief paper, we have a lot of information. It uses AT Math and Einstein’s Theory of Gravity. Space can be thought to be curved as the ball rolls in the roulette wheel. When the wheel spins fast enough, the Super force is reached and gravity is opposed to keep the ball suspended a the wheel edge. Einstein’s constant is 0/4233=Pi-e=cuz. We use the mechanics of the roulette ball course to model the universe. The result is a cardioid which converges on Euler’s Trig Identity and the Pythagorean Theorem.
Keywords: Oganessian; Benzene; AT Math.